GRL-0920, an Indole Chloropyridinyl Ester, Completely Blocks SARS-CoV-2 Infection - Hattori, Shin-ichiro; Higshi-Kuwata, Nobuyo; Raghavaiah, Jakka; Das, Debananda; Bulut, Haydar; Davis, David A.; Takamatsu, Yuki; Matsuda, Kouki; Takamune, Nobutoki; Kishimoto, Naoki; Okamura, Tadashi; Misumi, Shogo; et al. (mBio, 2020)
Targeting the main protease (M pro ) of SARS-CoV-2, we identified two indole-chloropyridinyl-ester derivatives, GRL-0820 and GRL-0920, active against SARS-CoV-2, employing RNA-qPCR and immunocytochemistry and show that the two compounds exerted potent activity against SARS-CoV-2. While GRL-0820 and remdesivir blocked SARS-CoV-2 infection, viral breakthrough occurred as examined with immunocytochemistry. In contrast, GRL-0920 completely blocked the infectivity and cytopathic effect of SARS-CoV-2 without significant toxicity. Structural modeling showed that indole and chloropyridinyl of the derivatives interacted with two catalytic dyad residues of M pro , Cys145 and His41, resulting in covalent bonding, which was verified using HPLC/MS. The present data should shed light on the development of therapeutics for COVID-19, and optimization of GRL-0920 based on the present data is essential to develop more-potent anti-SARS-CoV-2 compounds for treating COVID-19. We assessed various newly generated compounds that target the main protease (M pro ) of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and various previously known compounds reportedly active against SARS-CoV-2, employing RNA quantitative PCR (RNA-qPCR), cytopathicity assays, and immunocytochemistry. Here, we show that two indole-chloropyridinyl-ester derivatives, GRL-0820 and GRL-0920, exerted potent activity against SARS-CoV-2 in cell-based assays performed using VeroE6 cells and TMPRSS2-overexpressing VeroE6 cells. While GRL-0820 and the nucleotide analog remdesivir blocked SARS-CoV-2 infection, viral breakthrough occurred. No significant anti-SARS-CoV-2 activity was found for several compounds reportedly active against SARS-CoV-2 such as lopinavir, nelfinavir, nitazoxanide, favipiravir, and hydroxychroloquine. In contrast, GRL-0920 exerted potent activity against SARS-CoV-2 (50% effective concentration [EC 50 ] = 2.8 μM) and dramatically reduced the infectivity, replication, and cytopathic effect of SARS-CoV-2 without significant toxicity as examined with immunocytochemistry. Structural modeling shows that indole and chloropyridinyl of the derivatives interact with two catalytic dyad residues of M pro , Cys145 and His41, resulting in covalent bonding, which was verified using high-performance liquid chromatography–mass spectrometry (HPLC/MS), suggesting that the indole moiety is critical for the anti-SARS-CoV-2 activity of the derivatives. GRL-0920 might serve as a potential therapeutic for coronavirus disease 2019 (COVID-19) and might be optimized to generate more-potent anti-SARS-CoV-2 compounds. IMPORTANCE Targeting the main protease (M pro ) of SARS-CoV-2, we identified two indole-chloropyridinyl-ester derivatives, GRL-0820 and GRL-0920, active against SARS-CoV-2, employing RNA-qPCR and immunocytochemistry and show that the two compounds exerted potent activity against SARS-CoV-2. While GRL-0820 and remdesivir blocked SARS-CoV-2 infection, viral breakthrough occurred as examined with immunocytochemistry. In contrast, GRL-0920 completely blocked the infectivity and cytopathic effect of SARS-CoV-2 without significant toxicity. Structural modeling showed that indole and chloropyridinyl of the derivatives interacted with two catalytic dyad residues of M pro , Cys145 and His41, resulting in covalent bonding, which was verified using HPLC/MS. The present data should shed light on the development of therapeutics for COVID-19, and optimization of GRL-0920 based on the present data is essential to develop more-potent anti-SARS-CoV-2 compounds for treating COVID-19.